2013
DOI: 10.1186/1755-7682-6-38
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and visual stimulation effects on rectus femoris and biceps femoris muscles during isometric and concentric

Abstract: BackgroundCoactivation may be both desirable (injury prevention) or undesirable (strength measurement). In this context, different styles of muscle strength stimulus have being investigated. In this study we evaluated the effects of verbal and visual stimulation on rectus femoris and biceps femoris muscles contraction during isometric and concentric.MethodsWe investigated 13 men (age =23.1 ± 3.8 years old; body mass =75.6 ± 9.1 kg; height =1.8 ± 0.07 m). We used the isokinetic dynamometer BIODEX device and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…In contrast to our experienced sample of HIFT athletes, novice athletes may show greater differences in squat strength depending on technical and motivational deficiencies (Silva et al, 2013). In this regard, Argus et al (2011) stated that psychological interventions may have greater potential to affect performance in untrained or novice athletes.…”
Section: Discussionmentioning
confidence: 63%
“…In contrast to our experienced sample of HIFT athletes, novice athletes may show greater differences in squat strength depending on technical and motivational deficiencies (Silva et al, 2013). In this regard, Argus et al (2011) stated that psychological interventions may have greater potential to affect performance in untrained or novice athletes.…”
Section: Discussionmentioning
confidence: 63%
“…They assumed that maximal strength performance might not be sensitive enough to external verbal stimulation. Silva (43), found out that the verbal and visual stimuli alone were more effective in controlling the coactivation of the muscles during isometric contraction extension without changing the muscle strength. On the other hand, Lee (30) found that beginner athletes show greater changes in strength (4.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Knee moments are subject to sources of measurement error inherent to inverse dynamics (e.g., marker placement, skin motion artefact, error propagation by differentiating) 34 , and also influenced by footwear, gait speed and joint pain 35e37 . Strength and power may be affected by motivation, joint pain, and apprehension 38,39 . Load frequency and knee related quality of life were measured with the KOOS.…”
Section: Discussionmentioning
confidence: 99%